Transcriptomic and proteomic profiling reveal immune and metabolic dysregulation in the colonic mucosa of people living with HIV with incomplete immune recovery - Kaarbø, Mari; Yang, Mingyi; Meyer-Myklestad, Malin Holm; Sundaram, Arvind Y. M.; de Sousa, Mirta Mittelstedt Leal; Sharma, Animesh; Medhus, Asle W.; Dyrhol-Riise, Anne Margarita; Kvale, Dag; Hov, Johannes R.; Aukrust, Pål; Bjørås, Magnar; et al. (Frontiers in Immunology, 2025)
BackgroundPeople living with HIV are called immunological non-responders (INR) when their CD4+ T cell count is not restored to immunocompetent levels, despite successful viral suppression. INR have increased risk of progression to AIDS, non-AIDS related morbidity, and death. Impaired mucosal barrier function is a prevailing hypothesis for why INR among people with HIV (PWH) have persistently low CD4+ T cell counts.ObjectiveTo understand the molecular mechanisms behind incomplete immune recovery in INR, we analyzed gene regulation and protein expression in gut tissues from INR, immunological responders (IR) and healthy controls (HC).MethodsThe transcriptome was assessed by RNA-sequencing (RNA-seq) and the proteome was examined using shotgun proteomic mass spectrometry in mucosal biopsies from the sigmoid colon and terminal ileum.ResultsIn INR compared to IR, we identified 3326 differentially expressed genes (DEGs) in the colon while no DEGs were observed in the ileum. Gene ontology (GO) analyses revealed that the DEGs in colon of INR, compared to IR, predominantly involved pathways related to immune response, metabolism, and cellular processes. Notably, GO analysis highlighted downregulation of genes associated with B cell-mediated immunity and adaptive responses in INR. Deconvolution analysis indicated that these transcriptomic changes were not solely due to shifts in immune cell composition. Proteomic analysis supported these findings, showing more differential protein composition between INR and IR in colon than ileum. These proteins are associated with the regulation of adaptive immune signaling and essential cellular processes, including cell signaling, tissue repair, and growth, all of which are characteristic features of inflammatory bowel disease (IBD).ConclusionOur findings suggest that incomplete immune recovery during anti-retroviral therapy in PWH is associated with specific dysregulations in the molecular environment of the sigmoid colon, which may share mechanisms with IBD. The identified macromolecules may serve as potential targets for adjuvant treatment to improve the prognosis for INR.